Termaller Ve Cumulus'lerde Meteorolojik Parametrelerin Ölçülmesi, Analizi Ve Konvektif Yapının Modellenmesi - Aslan, Zafer (Fen Bilimleri Enstitüsü, 1987)
Bu çalışmada aşağı troposferde sıcaklık, bağıl nem, düşey hız, sıvı su miktarı gibi bazı meteorolojik parametrelerin yer ve zamanla değişimi deneysel ve teorik olarak incelenmiştir. Özellikle termaller ve sığ cumulus bulutlarının dinamik ve mikrofizik yapısı ve meteorolojik parametrelerin bu alanlarda nasıl değiştiği araş tırılmıştır. Termaller, yeryüzey inden yükselen ve çevrelerine göre daha sıcak bireysel hava kütleleridir. Bunlar arasında yoğunlaşma sevi yesine yükselecek kadar güçlü olanlar, cumulus bulutu haline dönüşür ler. Burada sadece, cumulus humilis ve cumulus mediocris gibi sığ bulutlar gözönüne alınmıştır. Bu araştırmada, ölçümler, 1983, 1985 ve 1986 yıllarında konvektif aktivitenin çok olduğu bahar ve yaz aylarında İnönü'de (Eskişehir) cumulus bulutları içinde ve çevrelerinde uçak ve planör lerle yapılmıştır. Bu ölçümlerde kullanılmak üzere bir sıvı su miktarı ölçeri de geliştirilmiştir. Verilerin analizinde öncelikle, meteorolojik elemanlar arasındaki ilişkiler araştırılmış, parametrelerin zaman ve yüksek likle olan değişimleri incelenmiş ve termal bölgelerinin belirlenmesi amacı ile bir kriter oluşturulmasına çalışılmıştır. Bu çalışmada ayrıca kütlenin korunumu, toplam nem eşitliği, toplam nemli statik enerji eşitliği ve momentumun korunumu eşitliklerinden hareketle 1-boyutlu teorik cumulus- termal modeli geliştirilmiştir. Bu modelde termallerin yeryüzeyinden itibaren r-yarıçaplı bir koni içinde yük seldiği kabul edilmiş ve entrainment (katılım) olayı gözönüne alın mıştır. Model, radyosonde verilerini kullanarak, çevre koşullarını ve buna dayanarak da termal veya cumulus içindeki parametreleri hesaplamaktadır. Modelden elde edilen sonuçlarla, gözlemlerin oldukça iyi bir şekilde uyuştuğu görülmüştür. Sonuç olarak, 1-boyutlu cumulus- termal modelinin cumulus bulutu ve termal bölgelerinde meteorolojik büyüklüklerin yükseklikle olan değişimlerinin tahmininde büyük bîr yaklaşıklıkla kullanılabileceği söylenebilir.

Cloud physics is one of the most complicated and important subjects in the atmospheric studies. Especially the convective clouds are more important compared to the other type of clouds since they contain quite a large portion of the atmospheric humidity. Convective motions within atmosphere appear as a consequence of the heat imported into the ground by the solar radiation. The upward motions of individual air masses, caused by locally heated ground surfaces in this way, is named generally as "thermals" and sometime as "blue-thermics". Some of these thermals gain sufficient energy to rise up to the level of condensation and become cumulus clouds that contain a conglomerate of water particles suspended within the humid air. While this formation of the cumulus clouds takes place, some energy discharged by the condensing water particles is redistributed within the forming cloud and creates an inner mechanism of motion which is called the cumulus circulation. The first investigations about the cumulus convection have been started off some fifty years ago. In the present time these studies form integral parts of the large projects auch as GARP (Global Atmospheric Research Programme) and GATE (GARP Atlantic Tropical Experiment). This thesis is intended to be a first attempt to initiate the cumulus convection studies by flying observations in Turkey and as such many practical difficulties, encountered and overcome during the actual experimentation phase, had a notiçable effect on the accuracy of the measurements. However, it should be stated that this, in fact, is the case almost with every investigation on this subject because of the overall cost and the necessity of waiting for the suitable weather conditions. The main goal of this study is to gain some insight about the micro-physical and dynamical structure of the thermals and shallow cumulus clouds. For this purpose the pertaining parameters.i.e. temperature, relative humidity, vertical air velocity and liquid water content have been measured within or in the vicinity of thermals, cumulus-humilis/cumulus-mediocris clouds, by flying through or around, With SIAT or CESSNA 207 airplanes or PUCHACZ-SZD-50 gliders. - vm The flight area is the İnönü (Eskişehir) Glider Base which is situated in the western part of the Internal Anatolia where temporal thermals have been noted and manipulated for many years in gliding. Because of the appreciable dominance of the convective activities, the spring and summer time has been preferred as the observation period. In the flight location and for the seasons stated above, the most of the developing thermals are the dry thermals within which the maximum vertical velocities are not higher than 1.5 m/sec and for this reason these thermals are named in the text as the weak or the moderate thermals. The first chapter of the thesis is devoted to a general survey of the relevant literature after stating the aim and the frame of the work presented. In the second chapter, the general theory on cumulus convection is outlined. The general technics of experimentation in flight, the measured atmospheric parameters, the measuring methods and the characteristics of the various gauges and their installation on aircraft etc. are discussed in the third chapter. A one-dimensional theoretical model for the cumulus clouds is presented in the fourth chapter together with the comparison of the experimental and theoretical results. Finally, some general conclusions and comments are given in the fifth and the last chapter. The third chapter of the thesis comprises of two sub-sections: The general detailed description of the experimentation technics and also the analysis of the data obtained. The recording of the- meteorological parameters (temperature, relative humidity, vertical air velocity and liquid water content), in the form of the averages obtained in the one minute time intervals, has been achieved by using a CR-21 micro-logger. Flight data, because of the technical difficulties in transfering them directly to the same recorder, had to be recorded seperately by using simultaneous photography from the control panel. Temperatures have been measured by a standard thermo-couple gauge and relative humidity by a relative- humidity-meter. The liquid water content measurements have been carried out by a specially designed and prepared electrical hot-wire system. The sensing elements of all these systems have been placed carefully on the outboard of the air-vessel so that the measurements were not affected by the turbulent noise created by the air-flow around. The vertical acceleration has been measured by a vertical accelerometer borrowed from a DC-9 aircraft. All of the measurements have been carried out by several special flight tests, such as butterfly path flights, for typical periods of 30-45 minutes. The liquid water content meter which has been described in detail in the third chapter, was designed and tested completely by the author. The calibration process has been performed in the wind-tunnels of the Aircraft Engineering Department and also of the Air Force Academy. This system is made of a porcelain rode wound by tw& ineef-wovan gpiyals of platinum wires each of one meter long. The wires are isolated from each other by a layer of LiCl which is - IX - sensitive to the environmental humidity variations. In order to prevent polarization, the wire is heated electrically by the application of a 24V alternative current supplied by a rechargable battery and converted by an alternating switch arrangement. The cumulus clouds are simulated in the wind tunnel, by the diffusion of pure water droplets ejected from a specially designed nozzle. The calibration is repeated under various temperatures and humidity conditions. This system has been tested in 1986, first time under the actual atmospheric conditions by taking a series of measurements in the lowest, highest and central levels of the clouds. During these studies, the amount of liquid, water content has been measured as varying between 0.5-1.2 g/m3 and having a positive gradiant in the lower portions but a negative gradiant in the higher portions. In the third chapter, in addition to the experimental technics used, the local changes in the meteorological parameters are studied in order to ascertain some criteria for determining the location of the thermals. It has been osberved that within the thermals the temperature, the relative humidity, the total static energy, the vertical velocity and the flight altitude display a trend to attain higher values than their respective mean values, as might have been expected. As a result of this study it is suggested in the thesis that a standart deviation of the order of 25 % in the total specific humidity and the total static energy has been found to be a suitahle criterium verifying the observations. But on the other hand the use of temperature levels, has been found inconclusive for this purpose, especially if any mixing is in presence. The detection of the thermals if a constant velocity level flight is realized, can also be made by the variometer on board, since it shows the relative sinking or elevating velocity of the vessel. The recording of this parameter provides the upward or downward velocity values within the thermals. Another subject which takes place in the third chapter is a discussion about the linear correlations between the measured parameters, The calculations have shown that these correlations are stronger in the thermals than the clouds. This hints to the fact that the micro- physical structure of the clouds is more complicated than that of the thermals. The strongest linear correlations within the thermals have been observed between the. total specific humidity- total static energy,. total specific humidity-relative humidity,. relative humidity- total static energy and also. temperature-relative humidity-total static energy. Last subject included in the third part is a statistical investigation on the experimental errors, where the reliability intervals of the measured parameters have been determined and presented in tables according to the 5 % or 10 % significance levels. The fourth chapter of the thesis begins with the theoretical study of the thermals., Using a simple one dimensional thermal-cumulus model, the basic equations, stating the conservations of mass, total static energy, total specific humidity and momentum have been formed and discussed. In this model the thermals and the cumulus clouds are - x - assumed to develop within an imaginary vertical cone having its apex at the ground level and a prescribed initial thermal radius of 100, 200, 500, 1000 and 2Q00 meters, and to gain height with the time in accordance with the assumption that the gradiant dr/dz is constant and equal to 0.25. This model provides a simple method for the calculation of meteorological parameters and this has been carried out for every 10 meters up to the level of the pressure value 700 HPa.. is reached. The initial vertical velocity and the temperature difference between the thermal and the environment have been assumed to be w = 1 m/sec and AT = 1°C respectively in the computations. The model considers the entrainment phenomenon in a limited way and assumes that the inclusion of external air masses to the developing thermal is possible only laterally that is through the cone surface. According to the results obtained with this method, the temperature decreases within the thermal or cumulus clouds with the altitude, and it is not greatly affected by the initial radius of the structure. The relative humidity increases with the height in the beginning and whence the saturation point is reached (some 2400-2500m) then the thermals transform into the cumulus clouds. The change of the total energy with the altitude displays a strong similarity to that of the total specific humidity. The vertical velocity values increases with the height but a decreasing trend is noted for greater altitudes. The formation of the cloud which is accompaihed by the appearance of the condensing water particles causes a reincrease in the vertical velocity and also in the liquid water content values within the lower part of the cloud. The comparison of the experimental results (of the third chapter) with the theoretical values obtained by this model forms the main material of this chapter. Generally the agreement obtained between the experimental and the theoretical results are quite satisfactory. For example in the case of temperature, relative humidity and the total energy the maximum deviation is less than 10 %. The discrepencies originate mainly from two sources: i) The crudeness of the experimental technics originating primarily by rather long time intervals between the subsequent data recordings, the sensitivity losses of the sensors within the clouds and of course the turbulence created by the propellers. ii) The simplifying assumptions of the theoretical model such as using a one-dimensional model (depending on the height only), presenting entrainment by mass addition through the cone surface, neglecting the droplet distribution and/or concentration within the cloud. There is also one special source of error that has to be mentioned. The İnönü Gliding Base has no radiosonde station. Hence all the environmental data used in the theoretical study had to be taken from the tables prepared by Ankara radiosonde station (which is situated some 250 kms to the east). Although, care is taken to make simultaneous flights, this fact obviously creates a certain amount of uncertainty in the theoretical results. - xi * As a final conclusion it can be stated, perhaps, that this work presents a beginning phase of the study of convective activities and cloud formation processes by "in-flight observations" in Turkey. The results are quite reliable and also comparable with the similar work obtained elsewhere in the world. However in order to further improve the results obtained in this thesis, following suggestions may be considered: i) To improve the existing experimentation technics and develop new methods. Especially the simultaneous recording of data using smaller time intervals has the first priority in this respect. Apart from this to increase the sensitivity of the humidity measurements a Lyman-Alpha Hygrometer or some similar more sophisticated gagdet must be used together with a better quality platinum-wire thermocouple for temperature measurements. Also a second (i.e. parallel) sensor, made of with copper wires for example for the liquid-water-content measurements may be integrated to the system to provide a possibility to check the accuracy of the existing system, as it is becoming a fairly common practice lately in measuring this quantity. ii) To improve the reliability of the recorded flight data, in addition to the exsisting variometer measurements, it is recommendable to use a gyroscopic accelerometer to measure the vertical acceleration together with the actual flight angle of attack, so that the flight mechanics equations may be used to obtain an independent set of data for the vertical velocity. iii) Another and a somewhat obvious improvement can be obtained by increasing the number of observation flights so that a more adequate amount of data can be processed statistically in order to assess the rate of development and the strength of thermals and the degree of convectivity within. iv) Theoretically, a better level of representation can be created by using a modified one-dimensional but an unsteady cumulus- thermal model instead of the present steady one. This work has been generously supported by DME (Governmental. Meteorological Organisation), TÜBİTAK (Turkish Scientific and Research Council MAG 649/A), THK (Turkish Air League) and ITU (Istanbul Technical University-Faculty of Aeronauticts and Astronautics), and the auther is greatly thankful.
Measurements And Analysis Of The Meteorological Parameters In Thermals And Cumulus Clouds And Mmodelling Of The Conventive Structure
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1987
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1987
Keywords: kümülüs; meteorolojik parametreler; termal; cumulus; meteorological parameters; thermal